Outcrops Conservation of Tanjung Baru or Lower Talang Akar Formation, Baturaja City of Palembang Area - South Sumatra Basin: How important? - Premonowati Premonowati (Ikatan Ahli Geologi Indonesia, 2011)
Tanjung Baru Formation only outcropped in one location so called Tanjung Baru, Palembang, South Sumatra. In total this formation is expossed in an area of about one acre. The outcrop is a quartz sandstone quarry, which has become smaller in size rapidly because of intensive mining activities by the local community. The formation is also called Gritsand Member (GRM) of the Lower Talang Akar Formation/Lemat Formation/Lahat Formation. A different name from Talang Akar Formation was given to this formation because it has an important role in the tectonostratigraphy context. Tanjung Baru Formations has different genetic, location and section type from that of Talang Akar Formation. The formation consists of conglomeratic sandstone of channel deposit. The sections indicate five times of channeling with each channel has a geometry of 20 m long and 9 m thick. This lag sedimentary deposit consists of fine- to very coarse-grained sandstones. The erosional base contact has polymictic conglomeratic sandstone outcrop with gradded bedding and planar crossbedding that indicate high energy deposition like channelized environment in shallow marine. The fining upward succession was a result of lateral accretion of channel shifting or a fluvial channel system depositional environment. The very fine sand of channel plug was deposited in a very low energy environment before the channel was abandoned. Some parts have shaly and coal streaks with mafic and feldspatic minerals. This formation has an indication to be an excellent reservoir.The geology of Tanjung Baru Formation is an important object to study because it is the one and only outcrop that needs to be conserved. The objective is to save this outcrop from extinction. A socialization to the Governor of South Sumatra Province and Head of Palembang Regent needs to be done. The government has to create a regulation to stop the mining activities, build a boundary for the outcrops with plantation and put an information board to explain that it’s a conservation area. Let all geology students and also people of all generations to have a possibility to learn Tanjung Baru Formation from this outcrop as a geopark.